Introducing a Special Series: Integration of Internationally Educated Nurses Into the Canadian Workforce - Alyssa Indar and Edward Cruz (Nursing Leadership, 2025)
Internationally educated nurses (IENs) are a growing segment of our Canadian health workforce. Nursing leaders are seeking examples of effective IEN integration programs to shape organizational policies and strategies to support IENs in their local context. In this special issue, we share national and international examples of successful IEN integration, authored by the nurses leading these programs. In the first issue, we profile examples of IEN integration in rural Manitoba and in an urban centre in Ontario. Both examples offer insights suitable for varied geographical and cultural contexts, with commonalities regarding the need for thoughtful and collaborative approaches to IEN program planning, implementation and evaluation.
Keywords: Internationally educated nurses Ontario, IEN integration strategies Canada, Supervised Practice Experience Partnership, Nursing orientation curriculum for IENs in Canada, Cultural humility in nursing education, Advanced Practice Nurse Educator role